Lifestyle and Risk Factors Related to Metabolic Syndrome in Administrative Workers: Universidad Nacional de Trujillo, Perú - Rodríguez-Salvatierra, Alvaro David; Bardales-Vásquez, Cecilia Betzabet; Martin-Alva, Enrique Aurelio; Lezama-Escobedo, Martha Karina; Gil-Ramírez, Luis Arturo; Medina-Vásquez, Katherine Marita Elizabeth; Vidal-Fernández, Jorge Leyser; León-Torres, Carlos Alberto (Journal of Ecohumanism, 2024)
Objective: To characterize the lifestyle and risk factors related to Metabolic Syndrome of administrative workers at the Universidad Nacional de Trujillo. Method: A total of 168 administrative workers from the main campus of the Universidad Nacional de Trujillo were selected in accordance with stratified random method. Results: In the Lifestyle Profile according to Pender (1996), 65.5% of the participants have a low level of exercise, and 82.1% manifest sufficient personal habits. Adults accounted for 67.9%, and the majority were overweight (47.6%). Regarding metabolic status, 54.2% were healthy, while 45.8% were identified with Metabolic Syndrome. In addition, the risk of becoming ill, according to waist circumference, was very high in 42.9% (72) of cases. Likewise, the risk of cardiovascular disease is higher in healthy people, while it is very high in workers with Metabolic Syndrome (p < 0.001). Moreover, workers with normal weight have a low risk of becoming ill, on the contrary, for those who are overweight it is high and those who are obese have a very high risk (p < 0.001). Conclusion: In terms of lifestyle, there was a low level of exercise, and most of the participants only had sufficient personal habits. Regarding the components linked to Metabolic Syndrome in the authoritative staff of Universidad Nacional de Trujillo, both men and women presented abdominal obesity, and the values of systolic and diastolic blood pressure, fasting glucose and triglycerides were altered. Furthermore, the women had HDL values below what was desirable. Regarding the risk of cardiovascular disease, it is very high in syndromic workers, those who are overweight are high, and obese workers are at very high risk.